Macroeconomic Stabilization of the Russian Economy during the years 1997-2012 - Walawski, Mirosław (Studia Oeconomica Posnaniensia, 2015)
All the world’s economies face the challenge of maintaining macroeconomic stability. In the case of post-socialist economies, the concept takes on a new meaning in terms of the transition period. Experience shows that when rebuilding the economy in such rapidly changing conditions, achieving an appropriate level of stabilization in the economy is not easy. The problem is finding the optimal relationship between the determinants of macroeconomic stability. In the early 1990s the Russian economy found itself facing new conditions and needed to adapt the entire economy to this new reality. One of the three elements of the transition is stabilization. The main objective of this paper is to analyse the process of macroeconomic stabilization for the Russian economy in 1997-2012. In this article the author uses the method of the macroeconomic stabilization pentagon (PSM), which made it possible to determine the stabilisation rate as well as analysing the process. The aim of the article is to assess the measures taken in terms of macroeconomic stabilization during the period analysed as well as attempting to verify the hypothesis that the proper coordination of economic policies leads to achieving a high level of macroeconomic stabilisation.